Download presentation
Presentation is loading. Please wait.
1
Submodularity Reading Group Polymatroid
M. Pawan Kumar
2
Submodular Function Ground set S Function f over power set of S
f(T) + f(U) ≥ f(T ∪ U) + f(T ∩ U) for all T, U ⊆ S
3
Diminishing Returns Define df(s|T) = f(T ∪{s}) - f(T)
Gain by adding s to T If f is submodular, df (s|T) is non-increasing df (s|T) ≥ df(s|U), for all T ⊆ U
4
A Clarification on Notation
Vector: x (in bold font) An element of the vector: xi (non-bold x) Consider ground set S = {1, 2, …, n} x(U) where U ⊆ S: ∑i∈U xi
5
Polymatroid Set S Submodular function f Real vector x of size |S|x1
Pf = {x ≥ 0, x(U) ≤ f(U) for all U ⊆ S} Polymatroid EPf = {x(U) ≤ f(U) for all U ⊆ S} Extended Polymatroid
6
Primal Problem max wTx x ∈ EPf Assume f(null set) ≥ 0
Otherwise EPf is empty f(null set) can be set to 0 Why? Decreasing f(null set) maintains submodularity
7
Primal Problem max wTx x ∈ EPf Assume w ≥ 0
Otherwise the optimal solution is infinity Why?
8
Greedy Algorithm max wTx x ∈ EPf
Order s1,s2,…,sn ∈ S such that w(si) ≥ w(si+1) Define Ui = {s1,s2,..,si} xGi = f(Ui) – f(Ui-1) xG ∈ EPf Proof?
9
Proof Sketch We have to show that xG(A) ≤ f(A) for all A ⊆ S
Trivial when A = null set Mathematical induction on |A|
10
Proof Sketch Let k be the largest index such that sk ∈ A
Clearly |A| ≤ |Uk| xG(A) = xG(A\{sk}) + xGk ≤ f(A\{sk}) + xGk Induction Why? = f(A\{sk}) + f(Uk) - f(Uk-1) Definition Why? ≤ f(A) Submodularity Why?
11
Greedy Algorithm max wTx x ∈ EPf
Order s1,s2,…,sn ∈ S such that w(si) ≥ w(si+1) Define Ui = {s1,s2,..,si} xGi = f(Ui) – f(Ui-1) xG is optimal Proof?
12
Dual Problem min ∑A yA f(A) max wTx yA ≥ 0, for all A ⊆ S x ∈ EPf
∑A yAvA = w Let us first try to find a feasible dual solution
13
Greedy Algorithm Order s1,s2,…,sn ∈ S such that w(si) ≥ w(si+1)
Define Ui = {s1,s2,..,si} yGUi = w(si) - w(si+1) yG is feasible yGS = w(sn) Proof? yGA = 0, for all other A
14
Proof Sketch Trivially, yG ≥ 0 Consider si ∈ S
∑A∋si yGA = ∑j≥i yGUj = w(si) ∑A yAvA = w
15
Optimality Primal feasible solution xG Dual feasible solution yG
Primal value at xG = Dual value at yG Proof?
16
Proof Sketch wTxG = ∑s∈S w(s)xGs = ∑i∈{1,2,…,n} w(si)(f(Ui) - f(Ui-1))
= ∑i∈{1,2,…,n-1} f(Ui)(w(si) - w(si+1)) + f(S)w(sn) = ∑A yGA f(A)
17
Optimality Primal feasible solution xG Dual feasible solution yG
Primal value at xG = Dual value at yG Therefore, xG is an optimal primal solution And, yG is an optimal dual solution
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.